Systemowe rozumienie uzależnienia w rodzinie - Peć, Bogdan (Wydział Teologiczny, UAM, 2012)
Uzależnienie jest chorobą wielowymiarową. Osoba zażywająca substancje psychoaktywne przeżywa wiele trudności intrapsychicznych, które motywują ją do podjęcia terapii odwykowej. Jednak w powstawaniu uzależnienia ważną rolę odgrywają relacje wewnątrzrodzinne. Analizując wiele przypadków pacjentów leczących się w Katolickim Ośrodku „Dom Nadziei” w Bytomiu, można określić swoisty model rodziny osoby uzależnionej. Terapia rodzin jest próbą analizy tego „patologicznego modelu”, a zarazem stwarza nową perspektywę, nową narrację funkcjonowania rodziny.

Addiction is a multidimensional disease. A person who takes psychoactive substances experiences numerous intrapsychic difficulties which motivate him/her to seek drug therapy. It must be remembered, however, that intra-family relations play an important role in the formation of addiction. Based on case study of the patients undergoing treatment at the Catholic Centre “Home of Hope” in Bytom it is possible to define a specific model of an addict’s family. The therapy of families is an attempt to analyze this “pathological model”, but at the same time it opens a new perspective, a new narration of the family’s functioning.
A Systemic Understanding of Addiction in the Family
Keywords: terapia rodzin; therapy of families; terapia uzależnień; therapy of addiction; system rodzinny; family system; uzależnienie; addiction